Multi-Format Document Verification System - Rajapashe, Madura; Adnan, Muammar; Dissanayaka, Ashen; Guneratne, Dasith; Abeywardena, Kavinga (American Scientific Research Journal for Engineering, Technology, and Sciences, 2020)
The spread of fake documents claiming to be from official sources on social media has led to increasing levels of skepticism and uncertainty in modern society. Currently, there is no easy access method of verification for documents that can be adopted by the public. This paper proposes a method of a multi-format document verification scheme using digital signatures and blockchain. We employ digital signature algorithms to sign document contents extracted using Optical Character Recognition (OCR) methods and attach this signature to the document by converting it into a 2D barcode format. This code can then be used on a shared document to retrieve the document’s digital signature and OCR can be used to verify the signature. In addition to this, we also provide an alternative method of verification in the form of forgery detection techniques. These signed documents are stored in a decentralized storage solution backed by blockchain technology, increasing the solution’s overall reliability and security.